1991
DOI: 10.1210/mend-5-5-709
|View full text |Cite
|
Sign up to set email alerts
|

Progestins Induce Down-Regulation of Insulin-Like Growth Factor-I (IGF-I) Receptors in Human Breast Cancer Cells: Potential Autocrine Role of IGF-II

Abstract: Insulin-like growth factor-I (IGF-I) receptors are present in breast cancer cells and may play a role in breast cancer cell growth. We have studied the effect of progestins on IGF-I receptors in T47D human breast cancer cells. T47D cells constitutively express high levels of progesterone receptors and are a model for studying the regulation of cellular functions by progestins. Treatment of T47D cells with either progesterone or the synthetic progestin promegestone (R5020) decreased IGF-I receptor content by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…These findings are consistent with the observed up-regulation of IGFR-I mRNA observed in MCF-7 breast cancer cells treated with E2 in our study and others (Stewart et al, 1990;Thorsen et al, 1992), and with the observed downregulation of IGFR-I mRNA observed in T47D breast cancer cells treated with Pg (Papa et al, 1991). These previous studies of E2 and Pg effects on IGFR-I showed that the changes in mRNA levels were reflected by equivalent changes in levels of the cell membrane receptor (Stewart et al, 1990;Papa et al, 1991). In the present study, we have not quantified the changes in cell surface IGFR-I concentrations.…”
Section: B4-fl and 36b4-r1 Respectively (See Materials And Methods)supporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with the observed up-regulation of IGFR-I mRNA observed in MCF-7 breast cancer cells treated with E2 in our study and others (Stewart et al, 1990;Thorsen et al, 1992), and with the observed downregulation of IGFR-I mRNA observed in T47D breast cancer cells treated with Pg (Papa et al, 1991). These previous studies of E2 and Pg effects on IGFR-I showed that the changes in mRNA levels were reflected by equivalent changes in levels of the cell membrane receptor (Stewart et al, 1990;Papa et al, 1991). In the present study, we have not quantified the changes in cell surface IGFR-I concentrations.…”
Section: B4-fl and 36b4-r1 Respectively (See Materials And Methods)supporting
confidence: 94%
“…The synergism between E2 and IGF-I in MCF-7 cells can be abrogated by adding the aIR-3 antibody, which prevents binding of IGFs to the IGFR-I (Thorsen et al, 1992). In another breast cancer cell line, T47D, treatment with progesterone (Pg) was found to decrease the expression of the IGFR-1, whereas it had no effects on the growth of the cells (Papa et al, 1991).…”
mentioning
confidence: 99%
“…Elevated expression of IGFR by the oestrogen-independent ZR-PR-LT line is consistent with the observation that another oestradiol-induced protein (PGR) is also overexpressed in this cell line in the absence of oestrogenic stimulation (Van den Berg et al, 1990). (Papa et al, 1991). However, a different cell line (T47D) and different progestins (progesterone and R5020) were used in the latter study and the down regulation of IGFR reported was attributed to a progestin-induced increase in IGF-II secretion.…”
supporting
confidence: 86%
“…Oestrogen has been reported to up-regulate IGF-I receptor (IGFR) expression, possibly sensitising tumour cells to the mitogenic effect of IGF-I (Stewart et al, 1990) and a positive relationship between oestrogen receptor (ER) and IGFR expression has been reported (Pekonen et al, 1988). Conversely, progestins appear to down-regulate IGFR numbers (Papa et al, 1991;Owens et al, 1993). Tamoxifen has been reported to reduce circulating levels of IGF-I (Pollack et al, 1992), and the pattern of expression of IGF binding proteins (IGFBPs), which can both attenuate and potentiate the actions of IGF-I, is influenced by both oestrogens and antioestrogens (Lonning, 1992;Owens et al, 1993;Lahti et al, 1994;Manni et al, 1994).…”
mentioning
confidence: 99%
“…Finally, progestogens have been reported to down-regulate IGF-l RNA message and content in breast cancer cell lines (Papa et al, 1991). If progesterone is the active agent then it might be that the concentration of this steroid is important and it would be predicted that patients treated in the midluteal phase, in which values of 20 ng ml-' occur, would have a better prognosis.…”
Section: Resultsmentioning
confidence: 99%